Social assessment of national parks through the example of the Aggtelek National Park - Kőszegi, Margit; Gessert, Alena; Nestorová-Dická, Janetta; Gruber, Péter; Bottlik, Zsolt (Hungarian Geographical Bulletin, 2022)
Karst areas, which are less involved in productive activities are often declared protected areas that can have a positive impact on the lives of the local communities. To verify this hypothesis, we examine karst areas, where national parks have been established to preserve mostly geological but also biological values. According to the threefold system of objectives in national parks, not only protection and conservation, but also the presentation of the natural values to the outside world is important. Thus, tourism and related services are essential and often exclusive economic activities in these protected areas. Our questions are how national parks appear in the daily lives of the local communities and how much locals perceive the beneficial effects of national parks. The selected area of our study is the Gömör-Torna / Gemer-Turňa Karst on the Hungarian-Slovak border, where national parks have been established on both side of the border (Aggtelek National Park in Hungary and Slovak Karst National Park in Slovakia) to preserve karst landforms and caves. We conducted structured interviews with leaders of settlements in and around the national park. Interviews reveal the ambivalent system of everyday relationships. Local communities are experiencing multiple conflicts with national parks. The conflicts stem from the contrast that usually occurs within the threefold system of objectives of national parks (the tension between the practice of protection/preservation and presentation). Locals are negatively affected by the presence of national park as an authority, which limits to some extent their economic activities. They perceive national parks as barriers that prevents them from building a more diversified economy, so the existence of the national park is seen by the majority as a disadvantage rather than an advantage. Some people even question the need to protect nature, which can be seen as a legacy of the former socialist regime. Thus, we conclude that there is a need to change the attitudes of local communities more positive towards nature conservation.